Review: Aplikasi Ekstrak Daun Kelor (Moringa oleifera) pada Berbagai Produk Olahan Daging - A. Apriantini; R. G. Putra; T. Suryati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Moringa Leaves (Moringa Oleifera) have high nutrition contents and bioactives substances, such as vitamins (B1, B2, B3, C, dan D), phenolic compounds, carotenoids, and nitrogen compounds. Therefore, Moringa leaves are often added to various processed meat products in order to increase the nutritional value and prevent oxidation reactions during product processing and storage. The aim of this study was to review the application of moringa leaves extract on processed meat products and study for their physicochemical, antioxidant, microbiological and sensory properties. The highest antioxidant activity measured using the DPPH method was found in using ethanol and methanol solvent with maceration techniques. Meat products that were added with Moringa leaf extract caused increased in antioxidant activity and protein content, reduced fat content and TBARS values, changed in pH, and increased in panelists’ preference if previously remove the unpleasant odors from Moringa leaves.